To Use Face Masks or Not After COVID-19 Vaccination? An Impact Analysis Using Mathematical Modeling - Kinyili, Musyoka; Munyakazi, Justin B.; Mukhtar, Abdulaziz Y. A. (Frontiers in Applied Mathematics and Statistics, 2022)
The question of whether to drop or to continue wearing face masks especially after being vaccinated among the public is controversial. This is sourced by the efficacy levels of COVID-19 vaccines developed, approved, and in use. We develop a deterministic mathematical model that factors in combination of COVID-19 vaccination program and wearing of face masks as intervention strategies to curb the spread of COVID-19 epidemic. We use the model specifically to assess the potential impact of wearing of face masks especially by the vaccinated individuals in combating further contraction of COVID-19 infections. Validation of the model is achieved by performing its goodness of fit to the Republic of South Africa’s reported COVID-19 positive cases data using the Maximum Likelihood Estimation algorithm implemented in fitR package. We firstly consider a scenario where the uptake of the vaccines and wearing of the face masks especially by the vaccinated individuals is extremely low. Secondly, we consider a scenario where the uptake of the vaccines and wearing of the face masks by people who are vaccinated is relatively high. Thirdly, we consider a scenario where the uptake of the vaccines and wearing of the face masks by the vaccinated individuals is on the upward trajectory. Findings from the scenario one and the scenario two respectively indicate highly surging number of infections and low recorded number of infections. For the scenario three, it shows that increased extent of wearing of the face masks by the vaccinated individuals at increasing levels of vaccine and face mask average protection results to highly accelerated decrease in the COVID-19 infections. However, wearing of face masks alone also results in the reduction of the peak number of the infections at increasing levels of face masks efficacy though the infections delay to clear.